Tool life assessment in end milling titanium alloy (Ti-6Al-4V) using PCD inserts - Turnad L., Ginta; Amin, A. K. M. Nurul; Lajis, M. A.; Karim, A.N. Mustafizul; Sutjipto, Agus Geter Edy (ILRAM Publisher, 2008)
This paper presents the investigation for assessment of tool life of PCD inserts in end milling of titanium alloy Ti-6A1-4V under dry conditions. Small central composite design (CCD) was employed to design the experiments and to develop the models which correlate tool life and the primary cutting parameters such as cutting speed, axial depth of cut and feed values. The range which is used in this study for cutting speed, axial depth of cut, and feed, are 80.5-200 m/min, 0.5-2.0 mm, and 0.05-0.15 mm/tooth, respectively. Design expert package software was employed to establish the tool life models and the adequacy of the models were verified using analysis of variance at 95% of confidence interval. From the models, it was affirmed that cutting speed has the most significant effect on tool life, followed by feed and axial depth of cut.